Educazione ed innovazione sociale L'apprendimento trasformativo nella formazione continua - Galeotti, Glenda (Studies on Adult Learning and Education, 2020)
This book proposes an interpretation of continuing education as an enabling factor of social innovation. Continuing education is an opportunity for transforming and co-creating structural and socio-cultural conditions in work contexts, through inclusive and collaborative practices and processes. The reflection presented in the book starts from an eco-systemic analysis of educational processes entailed in the social innovation dynamics, and develops a definition of educational action for formulating and testing responses to complex social needs. The educative action, oriented to creatively combine tangible and intangible resources, individual talents, collective imagination, improves capacity to rethink educational and socio-educational services and face the challenges that reality presents.